Morte e Vida em Cabaceiras: construção de um catolicismo popular peculiar no semiárido nordestino no âmago do binômio seca-morte, água-vida - Cavalcanti Filho, José Rocha (2015)
This thesis focuses on a region of the semi-arid northeast, Cabaceiras, State of Paraíba, which experiences the relentless struggle of its inhabitants seeking to survive on scarce water in long periods of drought. In their worship, dreaming of water and being tormented by the drought, they resist and go on building something that strengthens their faith and hope: a popular religiousness in the bosom of Catholicism. We studied the northeastern semi-arid and the drought/water binomial, the religious heritage in the wilderness between cultural tradition and the symbolic negotiation, Cabaceiras, its histories and stories. Finally, drought and the yearning for water in building popular Catholic religiousness in the region. It was found that it is a biomic religiousness that is impregnated by the savanna biome, the climate, penitence and at the same time devotion, family, prophesy - building and rebuilding itself constantly among the elements